THE EFFECTIVENESS OF LIFE SKILLS COUNSELLING IN IMPROVING STUDENTS’ SELF-REGULATED LEARNING - Faqih, Moh Mahfudz (PEDAGOGIK : JURNAL PENDIDIKAN, 2022)
Tremendous growth in technology, as part of the dynamics of globalization, can lead to gaps in student learning. Students tend to seek information and instant gratification through technological tools that have a major impact on their learning approaches, making it more difficult for them to be self-regulated learners. The aim of this study is to analyse the effectiveness of life skills counseling approach in enhancing the ability of self-regulated learning for high school students. This research is an experimental design by using randomized pretest-posttest with control group. The participants of this study consisted of 54 students of Senior High School level who were in the tenth grade. The data of the study were collected by the Scale of self-regulation in learning. Data analysis is used by two stages. First, data analysis for testing required statistical assumptions, ie test of data distribution normality with Kolmogorov-Smirnov test technique and homogeneity test of variance with Levene test. Second, data analysis for testing of research hypotheses conducted with Independent Sample t-test. The study shows that the life skills counseling has a meaningful effect on self-regulated learning. The average score of the experimental group was higher than the control group on all components of self-regulated learning.